Structural conservation of distinctive N-terminal acetylation-dependent interactions across a family of mammalian NEDD8 ligation enzymes - Monda, Julie K. (2012)
Little is known about molecular recognition of acetylated N-termini, despite prevalence of this modification among eukaryotic cytosolic proteins. We report that the family of human DCN-like (DCNL) co-E3s, which promote ligation of the ubiquitin-like protein NEDD8 to cullin targets, recognizes acetylated N-termini of the E2 enzymes UBC12 and UBE2F. Systematic biochemical and biophysical analyses reveal 40- and 10- fold variations in affinities amongst different DCNL-cullin and DCNL-E2 complexes, which contribute to widely ranging efficiencies of different NEDD8 ligation cascades. Structures of DCNL2 and DCNL3 complexes with N-terminally acetylated peptides from UBC12 and UBE2F illuminate a common mechanism by which DCNL proteins recognize N-terminally acetylated E2s, and how selectivity for interactions dependent on N-acetyl-methionine can be established through sidechains recognizing distal residues. Distinct preferences of UBC12 and UBE2F peptides for inhibiting different DCNLs, including the oncogenic DCNL1 protein, suggest it may be possible to develop small molecules blocking specific N-acetyl-methionine-dependent protein interactions.